2013
DOI: 10.1186/1471-2393-13-148
|View full text |Cite
|
Sign up to set email alerts
|

Developing a complex intervention for diet and activity behaviour change in obese pregnant women (the UPBEAT trial); assessment of behavioural change and process evaluation in a pilot randomised controlled trial

Abstract: BackgroundComplex interventions in obese pregnant women should be theoretically based, feasible and shown to demonstrate anticipated behavioural change prior to inception of large randomised controlled trials (RCTs). The aim was to determine if a) a complex intervention in obese pregnant women leads to anticipated changes in diet and physical activity behaviours, and b) to refine the intervention protocol through process evaluation of intervention fidelity.MethodsWe undertook a pilot RCT of a complex intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
154
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 56 publications
3
154
1
2
Order By: Relevance
“…Studies evaluating group-based interventions in other clinical settings have also reported positive feedback on this format of intervention delivery. 549,557,560 Therefore, although the group format was a reason for non-participation for some patients, those who attended the course enjoyed the format and engagement with other patients. This highlights an issue affecting many trials: a potentially biased sample because of the self-selection of participants with a preference for the intervention.…”
Section: Acceptability Of the Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating group-based interventions in other clinical settings have also reported positive feedback on this format of intervention delivery. 549,557,560 Therefore, although the group format was a reason for non-participation for some patients, those who attended the course enjoyed the format and engagement with other patients. This highlights an issue affecting many trials: a potentially biased sample because of the self-selection of participants with a preference for the intervention.…”
Section: Acceptability Of the Interventionmentioning
confidence: 99%
“…The logistics of scheduling group-based interventions is challenging, as many patients have limited availablity owing to other commitments. 538,549 Increasing flexibility in the scheduling of group-based interventions can be challenging, particularly within the financial constraints of a trial, but having the flexibility to run multiple courses is an important factor to consider when costing a trial.…”
Section: Acceptability Of the Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISRCTN89971375). A pilot RCT in 183 women to determine if the intervention led to changes in physical activity and diet was completed in 2011 [32]. Research Ethics Committee approval was obtained for the trial (UK Integrated Research Application System reference 09/H08-2/5), and all participants provided written informed consent to participate in the trial.…”
Section: The Uk Pregnancies Better Eating and Activity Trialmentioning
confidence: 99%
“…Los profesionales sanitarios, ante los cambios fisiológicos que se producen durante el embarazo, se vuelven cautos a la hora de prescribir el ejercicio físico (4,5). Este incierto criterio da lugar, según reporta la literatura, a que se incrementen las tasas de inactividad física durante el embarazo que oscilan entre el 64,5% y el 91,5%, y tienden a aumentar en el tercer trimestre del embarazo (6).…”
Section: Introductionunclassified